SUPERVISI KOLEGIAL MELALUI MGMP SEBAGAI UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU MATA PELAJARAN FISIKA SMA DI KOTA PONTIANAK - Elfi Husniwati; Usman Radiana; Sukmawati Sukmawati (Universitas Tanjungpura, 2022)
This study aims to describe the planning, implementation, evaluationand follow-up of collegial supervision at the MGMP Physics of SMAPontianak City. The form of the research used is a qualitative casestudy approach. The research subjects were seven people aged over40 years, working period of more than 10 years, consisting of two menand five women with the type or status in the MGMP consisting of achairperson, secretary, treasurer, three members and a supervisorysupervisor. All subjects were actively involved in MGMP activities.Data collection methods used interviews, document studies andobservation. Data analysis used an interactive model, namely datacollection, data reduction, data presentation and conclusion drawing.Test the validity of the data using source triangulation and techniquetriangulation. The main findings of the study are as follows: 1)Planning is carried out according to stages but the needs analysis isnot optimal, 2) The implementation of collegial supervision of teacherassistance and guidance services for other teachers is appropriatebecause it involves teachers in all aspects ranging from managers,implementers, participants and resource persons and meet serviceindicators, 3) Evaluation has met the correct stages, carried out by allmembers accompanied by supervisory supervisors, and 4) Follow-upis carried out by finding the cause of the problem, finding solutions,reporting activities and coaching. The conclusion is that collegialsupervision has been carried out by MGMP with implications forincreasing the professional competence of high school physicsteachers in Pontianak City.